Ruang kelas virtual: pembelajaran dengan pemanfaatan permainan online Hago - Maulana Reza Palevi; Pipit Amalia Saputri; Rian Vebrianto (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2020)
Game users today have a lot, ranging from children to adults. Even parents are now starting to play the game as free time to get rid of boredom. Online games are now a favorite for users. The Hago application not only presents a number of game options, but the application can be used in the world of education, such as the use of chat rooms with several menu choices in it. With the chat room feature, users can communicate remotely, especially students and teachers in terms of learning. The purpose of this study is to describe the use of Hago chat Room as a virtal classroom for students. The type of research is descriptive qualitative. The data in the form of recorded chat room user conversations, while the data source in this study is the chat room menus in Hago. Data collection techniques are done by recording several menus in the chat room and data analysis techniques, namely analyzing the menus in the chat room into a virtual classroom. The results showed that the chat room has benefits in the world of education, namely virtual classrooms by utilizing the menus in the chat room.